A Maqasid al-Shariah Framework for Fintech and Digital Asset Regulation in Muslim Jurisdictions - Elman Azizov; Adalat Azizov; Aytan Azizli; Aydin Anar Babayev (Journal of Islamic Law and Legal Studies, 2025)
This study examines how a Maqasid al-Shariah framework can provide a holistic and ethically grounded foundation for regulating fintech and digital assets across Muslim jurisdictions. Drawing upon classical Islamic legal sources and contemporary fintech literature, the research employs a qualitative library-based methodology to analyze how principles such as ḥifẓ al-māl (protection of wealth), maslahah (public welfare), and harm prevention can guide effective oversight of emerging technologies. Findings indicate that rapid digital financial innovation—particularly involving AI-driven platforms, blockchain systems, P2P lending, crypto-assets, and digital banking—poses significant regulatory challenges related to Shariah compliance, cybersecurity, financial stability, and consumer protection. Muslim jurisdictions face fragmented regulatory structures, inconsistent Shariah interpretations, and limited digital literacy, which hinder the development of cohesive governance frameworks. Integrating Maqasid al-Shariah provides an ethical compass to balance innovation with justice, transparency, accountability, and socio-economic welfare. The study highlights the need for harmonized cross-border standards, robust Shariah governance systems, AI ethics protocols, and regulatory sandboxes tailored to Islamic fintech. Ultimately, the Maqasid framework offers a dynamic and future-ready model for guiding digital finance ecosystems towards ethical resilience, social justice, and sustainable development.